Experimental Behavior of Concrete-Filled Steel Tubular Members Subjected to Lateral Loads - Chengzhi Wang; Xin Liu; Pengfei Li (Advances in Materials Science and Engineering)
The findings of an experimental study that was undertaken to investigate the performance of concrete-filled steel tubular members subjected to lateral loads are reported in this study. Columns of pure concrete, concrete with reinforcing bars, and two steel tube thicknesses were considered. Two different tests were conducted in this study. One test is used to research the performance of steel tube-reinforced concrete model piles under a lateral loading. The other test is used to research the effect of the depth of rock embedment for piles embedded in a foundation to simulate actual engineering applications in an experimental study. According to these test results, a detailed analysis was carried out on the relationships, such as the stress-strain and load-displacement relationships for the specimen. These tests show that the steel tube thickness and steel bars will significantly enhance the lateral bearing capacity and rigidity of the composite components. Additionally, the ultimate bending moment formula of a steel tube-reinforced concrete pile is deduced. The comparison of the calculated results with the experimental results shows that this formula is applicable for this type of pile foundation.